Pengaruh Organizational Trust terhadap Kesiapan Individu untuk Menjalankan Perubahan Sistem Manajemen SDM di PT “X” Bandung - Indah Puspitasari (Universitas Kristen Maranatha, 2018)
The aim of this study was to analyze the roles of organizational trust on the individual readiness for HR management system change at PT